Role of peri-deployment right ventricular paced-ECG in left bundle area pacing - Tang, Wen-De; Lu, Chiung-Ray; Wu, Mei-Yao; Chang, Ching-Fen; Chung, Wei-Hsin; Chen, Yin-Huei; Wu, Hung-Pin; Yip, Hei-Tung; Chang, Kuan-Cheng; Lin, Yen-Nien (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLeft bundle area pacing (LBBAP) has emerged as a promising physiological pacing modality. The current technique for LBBAP lead implantation predominantly relies on the anatomy of the His bundle and right ventricular septum. While practical, this anatomical approach can lead to variations in lead polarity and QRS durations due to the relatively extensive target zone.ObjectivesThis study aims to investigate whether peri-deployment paced ECGs can effectively guide LBBAP and enhance left ventricular activation.MethodsWe conducted a retrospective analysis of 41 patients (54 attempts) who underwent LBBAP between 1 September 2020 and 30 June 2021. We collected and analyzed demographic data, baseline ECGs, intraprocedural ECGs, and ventricular local electrograms. QRS patterns were categorized into five common types, R, Rs, rs, rS, and S, and were labeled from 1 to 5 for polarity analysis. In addition, we explored markers associated with achieving shorter QRS durations (<120 ms).ResultsLBBAP was successfully achieved in 81.5% of the attempts. During the procedure, the paced QRS duration (QRSd) significantly decreased from 144.5 ± 22.6 ms–128.8 ± 22.9 ms (p < 0.001). Comparing lead polarity scores before and after deployment revealed a significant increase in leads I and aVL (lead I, 1.3 ± 0.9 vs. 1.6 ± 1.0, p = 0.002; lead aVL, 1.6 ± 1.0 vs. 2.1 ± 1.3, p = 0.002), while leads III and aVF showed a decrease (lead III, 3.9 ± 1.2 vs. 3.4 ± 1.5, p = 0.001; lead aVF, 3.1 ± 1.2 vs. 2.9 ± 1.3, p = 0.026). The polarity of leads II and aVR remained unchanged. In the subgroup with post-deployment QRSd shorter than 120 ms, although the Qr pattern in lead V1 was only numerically higher (95.2% vs. 81.8%, p = 0.310), the lead polarity scores were significantly higher in leads I and aVL and lower in leads III and aVF (p < 0.001). This group also had a significantly shorter left ventricular activation time (LVAT) (68.7 ± 13.0 ms vs. 98.4 ± 14.0 ms, p < 0.001). Univariate analysis revealed that a shorter pre-deployment paced QRSd and LVAT were associated with a narrower post-deployment QRSd. In addition, non-electrical factors such as female gender and left ventricular dilation were associated with higher post-deployment QRSd.ConclusionsPeri-deployment ECG assessment is a practical adjunct to anatomy-based LBBAP, providing real-time markers for optimal lead positioning. Specifically, an unaltered lead II axis and expected changes in the lead I/aVL and lead III/aVF axes can help guide the selection of the left bundle branch. Lower pre-deployment paced QRSd and LVAT, as well as a more rightward inferior axis after deployment, are associated with a shorter post-deployment QRSd.